2009
DOI: 10.1002/ejoc.200801025
|View full text |Cite
|
Sign up to set email alerts
|

Cesium (Z)‐2‐Carbomethoxyethenethiolate: A Reagent for the Preparation of (Z)‐2‐Carbomethoxyethenyl Thioethers Including Selected Cysteine and Homocysteine Derivatives

Abstract: As a means to circumvent the standard and sometimes troubling conjugate addition reaction of thiols to alkyl propiolates, a new reagent, cesium (Z)‐2‐carbomethoxyethenethiolate, is introduced. The cesium carbonate mediated methanolysis of (Z)‐2‐carbomethoxyethenyl thiolacetate at low temperature creates cesium (Z)‐2‐carbomethoxyethenethiolate in solution. For base‐insensitive and solvolytically stable electrophiles, efficient substitution can be achieved by direct introduction to the electrophile. The conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The deprotection of a thioacetic acid-propiolate Michael adduct with CsCO 3 has also been used as an efficient route to vinylic thioethers including cysteine and homocysteine derivatives (Scheme 10). 129 It is interesting to note that subsequent intermolecular reactions were not reported despite the nucleophilicity of the thiolate species. The thiol-yne reaction was also not quantitative (yield = 79%) in this example despite the low pKa of the thiol, but this can be rationalized by the fact that it is a secondary thiol and imidazole is a relatively poor base.…”
Section: Bioconjugationmentioning
confidence: 99%
“…The deprotection of a thioacetic acid-propiolate Michael adduct with CsCO 3 has also been used as an efficient route to vinylic thioethers including cysteine and homocysteine derivatives (Scheme 10). 129 It is interesting to note that subsequent intermolecular reactions were not reported despite the nucleophilicity of the thiolate species. The thiol-yne reaction was also not quantitative (yield = 79%) in this example despite the low pKa of the thiol, but this can be rationalized by the fact that it is a secondary thiol and imidazole is a relatively poor base.…”
Section: Bioconjugationmentioning
confidence: 99%
“…Barua and coworkers [16] have already demonstrated that arenesulfenyl chlorides add across the triple bond of 3‐ p ‐bromophenyl‐2‐propynol in yields >55 %. Comparable trials with 1 c , the sulfenyl chloride possibly accessible from ( Z )‐2‐carbomethoxyethenyl thiolacetate [17] did not produce sulfinyl allene. Clearly the common protocols for making sulfenate esters and hence alkyl allenyl sulfoxides are not suitable for the planned chemistry.…”
Section: Resultsmentioning
confidence: 88%
“…Z,E-and Z,Z-bis [2-carbomethoxyethenyl] sulfoxides (2j) and homocysteine derivative 2l were prepared using the newly introduced caesium 2-Z-carbomethoxyethenethiolate methodology. 21 Other methods may be suitable for the preparation of the requisite sulfoxides 2, such as the sulfenic addition protocol of Aversa et al, 22 which would yield selectively the E-isomer, but this was not exploited for the current work.…”
Section: Resultsmentioning
confidence: 99%